COMPARATIVE EFFECT OF PLANTING MEDIA ON THE GROWTH OF ROBUSTA COFFEE SEEDLINGS (Coffea canephora L) - Kadha, Faustinus; Neonbeni , Eduardus Y (Universitas Veteran Bangun Nusantara, 2025)
The selection of an appropriate growing medium significantly affects the growth and quality of robusta coffee seedlings, which ultimately influences the success of cultivation and coffee plant productivity. This study aimed to investigate the effects of different ratios of growing media composed of soil, rice husk charcoal, and compost on the development of robusta coffee seedlings (Coffea canephora L.). A completely randomized design with five treatment combinations of growing media—M1 (1:1:2), M2 (1:2:2), M3 (1:2:3), M4 (1:3:2), and M5 (1:2:1)—was applied, each replicated six times. The measured parameters included plant height, number of leaves, stem diameter, root number, root length, as well as fresh and dry weight of the seedlings, observed between 30 and 96 days after planting. Analysis of variance was used to assess the treatment effects on seedling growth. Results revealed that treatment M3 significantly produced the greatest plant height (13.65 cm) and stem diameter (5.57 mm), while M5 excelled in root number (21.67) and root length (21.42 cm). Statistically, the growing media had significant effects on plant height, stem diameter, and root characteristics, but no significant impact on fresh and dry weights. Specific media combinations created optimal physical and chemical conditions by enhancing aeration, water retention, and the availability of macronutrients such as nitrogen, phosphorus, and potassium. In conclusion, the growing medium with a soil:rice husk charcoal:compost ratio of 1:2:3 was the most effective for promoting vegetative growth of robusta coffee seedlings. Keywords: Compost, Coffea canephora, Growing media, Rice husk charcoal, Robusta coffee, Seedling growth